2012
DOI: 10.1258/ijsa.2011.011218
|View full text |Cite
|
Sign up to set email alerts
|

The cost of managing genital warts in the UK

Abstract: The national cost of managing genital warts (GWs) in the UK has not been fully estimated, yet is required to inform decisions on vaccination against human papillomavirus. This study estimated the 2010 UK costs based on secondary genitourinary (GU) medicine clinic data from the Health Protection Agency (HPA) and primary care data from the Health Improvement Network database. Extrapolating data to 2010 resulted in 173,077 GU medicine clinic and 16,782 primary care GW episodes. Using treatment patterns obtained f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…The estimates for the unit cost for a single GWs event are highly variable, depending on the type of episode (first occurrence, recurrent or persistent GWs), the management setting and type of consultation [general practice, genitourinary medicine (GUM), hospital, etc. ], as well as the therapy used (medical treatment vs. surgery or other modalities) [ 7 , 8 ]. A recent study in Italy reported that the most frequent cause for HPV-related hospitalization was GWs [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The estimates for the unit cost for a single GWs event are highly variable, depending on the type of episode (first occurrence, recurrent or persistent GWs), the management setting and type of consultation [general practice, genitourinary medicine (GUM), hospital, etc. ], as well as the therapy used (medical treatment vs. surgery or other modalities) [ 7 , 8 ]. A recent study in Italy reported that the most frequent cause for HPV-related hospitalization was GWs [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Anogenital wart disease is the most common sexually transmitted disease, affecting millions worldwide every year. In 2010, approximately 190,000 new and recurrent cases were reported through GU clinics in the UK [1], with the low-risk HPV types (LR-HPV) 6 and 11 predominating in the pathogenesis of the common anogenital wart, or condyloma acuminatum [2]. The licensing of the prophylactic quadrivalent vaccine Gardasil (Merck) in 2007, which conveys protection against HPV types 6 and 11 in addition to the high-risk types HPV 16 and 18, has now raised the real prospect of reducing the disease burden of anogenital warts in society.…”
Section: Introductionmentioning
confidence: 99%
“…The UK has recently selected the quadrivalent HPV vaccine as part of its immunisation programme for 2012. The annual cost of wart disease diagnoses and treatments to the NHS in the UK is thought to be as high as £52.4 million [1]. …”
Section: Introductionmentioning
confidence: 99%
“…Treatment has a significant morbidity and can be frustrating, and recurrences are common. This causes psychosocial distress to patients and results in substantial financial costs [6, 7]. GWs result from persistent infection with low-risk HPV genotypes, predominantly 6 and 11, although other low-risk types were not evaluated in the former study [8, 9].…”
mentioning
confidence: 99%